2022
DOI: 10.1063/5.0080177
|View full text |Cite
|
Sign up to set email alerts
|

Kansei engineering and product-service systems (KEPSS) integrative framework for customer-centered experience

Abstract: This study introduces a conceptual integrative framework of Kansei Engineering (KE) and product-service systems (PSS) for customer-centered experience, known as KEPSS. Product or service alone is sometimes difficult to judge. With respect to more complex mixture of product and service experience, more comprehensive method is required to understand the total customer experience better. Usability or functionality with full of cognitive process is insufficient.Recent study shows that affect or Kansei is found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The traditional KE methodology focused more on the domain of product design (Hartono and Chuan, 2011;Conti et al, 2019), it lacks considerations for other PSS design elements. Later, the KE methodology has been proposed for PSS design by Carreira et al (2013) and Hartono (2022), thus it has been proven to be applicable to PSS design. In order to ensure that the KE methodology meets PSS design requirements, this study has constructed a new design framework named Extended Kansei Engineering (EKE) methodology through literature research, as shown in Figure 2.…”
Section: Extended Kansei Engineering (Eke) Methodologymentioning
confidence: 99%
“…The traditional KE methodology focused more on the domain of product design (Hartono and Chuan, 2011;Conti et al, 2019), it lacks considerations for other PSS design elements. Later, the KE methodology has been proposed for PSS design by Carreira et al (2013) and Hartono (2022), thus it has been proven to be applicable to PSS design. In order to ensure that the KE methodology meets PSS design requirements, this study has constructed a new design framework named Extended Kansei Engineering (EKE) methodology through literature research, as shown in Figure 2.…”
Section: Extended Kansei Engineering (Eke) Methodologymentioning
confidence: 99%
“…Kano model is used to identify and map out the level of service attribute performance based on customer experience and evaluation. Moreover, other quality and product/service development tools and methodologies were also integrated, such as, Quality Function Deployment (QFD), Design Thinking (DT), Taguchi, and mining process (Hartono, 2022). QFD is bridging the customer needs (named as WHAT) and physical design characteristics (named as HOW).…”
Section: Kansei Engineering Updatesmentioning
confidence: 99%